Jesus' Transformative Dialogue Model In John 1-4 - Lucky Antonio (International Perspectives in Christian Education and Philosophy, 2024)
The model of Jesus' transformative dialogue in the Gospel of John 1-4, describes the interaction of Jesus Christ conducting evangelism consistently through dialogues in John 1-4 with various figures in different contexts that lead to changes in understanding and spiritual transformation both individually and in the groups He faces. This study aims to identify and analyze the model of transformational dialogue carried out by Jesus Christ in John 1-4 to achieve the transformative goal of building relationships that enable the growth of faith among His listeners and bring people to faith in Him. The research method uses qualitative descriptive and exploratory text analysis with a hermeneutical approach to understand the cultural and theological contexts that underlie each effective missiological dialogue. This study analyzes six dialogues in John 1-4, involving Jesus Christ in conversation with four different groups of people. Dialogues as a means of communication to bring about change and deeper understanding of spiritual truth. The results of this study illustrate that Jesus Christ uses various dialogical strategies to convey the gospel message effectively to people from diverse social backgrounds to build relationships that enable the growth of faith. The transformational dialogue model of Jesus Christ in John 1-4, demonstrates wise and open dialogue in the context of evangelism and provides valuable teaching and guidance for modern evangelism practice and emphasizes the need for adaptation to the individual's social context to achieve maximum effectiveness in bringing people to Christ.